Can Support for Homosexuality Reduce the Prevalence of Mental Health Problems among LGBTQ+ Individuals to Levels Comparable to the General Population? A Second-Order Systematic Review with Thematic Analysis - Reza Payami Golhin; Seyyed Ali Marashi (Iranian Journal of Psychiatry)
Objective: This article addresses whether extensive support for homosexuality—accompanying its increased prevalence—has been able to reduce the prevalence of mental disorders among homosexuals in supportive countries to normal population levels. Method: This study was conducted in two phases. The first phase employed a secondary systematic review method and examined 68 reviews on the public health and mental health of homosexuals in supportive countries. In the second phase, using the thematic content analysis method, the semantic units extracted from the articles were condensed under sub-themes, which then formed themes at a higher level. Results: Supporting homosexuality has not reduced mental health issues in this group to levels observed in the general population, even in supportive countries. In addition to minority stress, other stressors (such as infectious diseases, cancer, childlessness, and the pathologic nature of homosexuality) are the main barriers to reducing the prevalence of mental disorders among homosexuals. Conclusion: Based on these findings, this study suggests revisiting the policy of extreme support for homosexuality and preventing scientific research concerning the correlation between this behavior and criminality and other mental disorders—under the pretext of homophobia.